Hydrographic characterization of an estuarine tidal channel - Vaz, N.
The hydrography of the Espinheiro channel, an estuarine tidal channel located within Ria de Aveiro (Portuguese northwest coast), is investigated using the analysis of a thermohaline variables data set as function of two main forcing factors: incoming river flow and tide. Salinity and water temperature vertical profiles were measured twice a month from September 2003 to September 2004 at ten stations along the channel. Furthermore, in order to characterize the upper fluvial region of the channel in terms of these variables, thermohalinepropertiesandcurrent speedwerealsomeasured duringtwotidal cyclesatananchorstationnear thechannel'shead.The salinity distribution along the channel is closely related to the incoming river flow and tidal propagation. The water temperature distribution is related to the freshwater temperature seasonal variations and, due to the shallowness of the study area, is also related to the meteorological conditions. Empirical Orthogonal Functions (EOFs) are used to study the salinity and water temperature variations along the channel. The analysis reveal that the first EOFaccounts for 87 and 97% of the total variance in vertically average salinity and water temperature, respectively. The temporal variation of the first EOF of the mean salinity and water temperature (PC1) is well correlated to the freshwater inflow ( − 0.86) and freshwater temperature (0.79), respectively. Formation of strong salinity gradients has been found in a region between 7 and 8 km from the lagoon's mouth. These strong gradients migrate within a region of about 1 km depending on the tidal regime: neaps or springs and its formation is related to changes in the channel's morphology (depth and width).